2016
DOI: 10.1038/ncomms10201
|View full text |Cite
|
Sign up to set email alerts
|

A cell cycle-dependent BRCA1–UHRF1 cascade regulates DNA double-strand break repair pathway choice

Abstract: BRCA1 is an important mediator of the DNA damage response, which promotes homologous recombination (HR) and antagonizes 53BP1-dependent non-homologous end joining in S/G2 phase. But how this is achieved remains unclear. Here, we report that the E3 ubiquitin ligase UHRF1 (Ubiquitin-like, with PHD and RING finger domains 1) directly participates in the interplay between BRCA1 and 53BP1. Mechanistically, UHRF1 is recruited to DNA double-strand breaks (DSBs) by BRCA1 in S phase, which requires the BRCT domain of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
127
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 107 publications
(129 citation statements)
references
References 69 publications
0
127
1
1
Order By: Relevance
“…Recent studies demonstrated that the function of UHRF1 in DNA repair is independent of its role in epigenetic regulation and identified a role for UHRF1 in regulating replication block bypass via PCNA-associated factor 15 (PAF15) ubiquitination (39,40). The Uhrf1 Zp3 cKO GV oocytes and 2-cell embryos displayed abundant nuclear g-H2AX signals compared with controls.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated that the function of UHRF1 in DNA repair is independent of its role in epigenetic regulation and identified a role for UHRF1 in regulating replication block bypass via PCNA-associated factor 15 (PAF15) ubiquitination (39,40). The Uhrf1 Zp3 cKO GV oocytes and 2-cell embryos displayed abundant nuclear g-H2AX signals compared with controls.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent dissociation of RIF1 from 53BP1, an antagonized effector of BRCA1, resulted in inhibition of NHEJ repair system and thus initiation of homologous recombination. 70 Involvement of UHRF1 in double-strand repair pathway was also shown in esophageal squamous cell carcinoma, where inhibition of UHRF1 downregulated endogenous levels of Ku heterodimer protein complex (Ku70/Ku80) which is well known to catalyze NHEJ DNA repair. 71 …”
Section: Involvement Of Uhrf1 In Dna Repairmentioning
confidence: 96%
“…For example, BRCA1 disrupts the interaction of 53BP1 and RIF1 in S/G2 phases by promoting dephosphorylation of 53BP1 by the PP4C phosphatase and targeting RIF1 by an E3 ubiquitin ligase UHRF1 (Isono et al 2017, Zhang et al 2016). BRCA1 also induces the exclusion of 53BP1 from the core of DNA damage foci in S/G2 phases (Chapman et al 2012a, Kakarougkas et al 2013).…”
Section: Brca1 Regulates End Resection–dependent Double-strand Brementioning
confidence: 99%